Safety of Infusing Ipilimumab Over 30 Minutes - Momtaz, Parisa (J Clin Oncol, 2015)
PURPOSE: The approved dose of ipilimumab is 3 mg/kg infused over 90 minutes; however, in clinical trials, 10 mg/kg has also been infused over 90 minutes. At this higher dose, patients receive 3 mg/kg within the first 27 minutes of treatment. We sought to determine whether the standard dose of 3 mg/kg could be safely infused over 30 minutes. METHODS: We reviewed retrospectively the incidence of infusion-related reactions (IRRs) to ipilimumab at our institution in patients receiving doses of either 3 or 10 mg/kg infused over 90 minutes. Our findings led to a change in institutional guidelines for ipilimumab infusion time from 90 minutes to 30 minutes. We reviewed the first 14 months of our prospective experience using a 30-minute infusion of ipilimumab. RESULTS: Between April 1, 2008, and June 30, 2013, 595 patients received 2,507 doses of ipilimumab infused at either 3 mg/kg (n = 457) or 10 mg/kg (n = 138) over 90 minutes. Although the 10 mg/kg group had a higher incidence of IRRs (4.3%) than the 3 mg/kg group (2.2%), this difference was not statistically significant (P = .22). In 120 patients treated prospectively with ipilimumab 3 mg/kg infused over 30 minutes, seven patients (5.8%) had an IRR (P = .06 compared with 90-minute infusions). All IRRs occurred at dose 2; six were grade 2, and one was grade 3. All seven patients received subsequent doses of ipilimumab safely, the majority with premedication. CONCLUSION: Ipilimumab at 3 mg/kg can be infused safely over 30 minutes with an acceptably low incidence of IRRs. After an IRR, patients can safely receive additional doses of ipilimumab with premedication.